2014
DOI: 10.1093/scan/nsu137
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent neighborhood quality predicts adult dACC response to social exclusion

Abstract: Neuroimaging studies using the social-exclusion paradigm Cyberball indicate increased dorsal anterior cingulate cortex (dACC) and right insula activity as a function of exclusion. However, comparatively less work has been done on how social status factors may moderate this finding. This study used the Cyberball paradigm with 85 (45 females) socio-economically diverse participants from a larger longitudinal sample. We tested whether neighborhood quality during adolescence would predict subsequent neural respond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 92 publications
3
22
0
Order By: Relevance
“…In contrast, the original sample consisted of almost exclusively white, highly satisfied married couples from Madison, WI. Within the sample discussed here, we have already observed that lower adolescent neighborhood quality corresponded with increased prefrontal and dACC activation to a social exclusion task ( Gonzalez et al , 2015 ). Others have reported that lower social status is linked to threat-related appraisals of ambiguous social stimuli (e.g.…”
Section: Discussionsupporting
confidence: 52%
“…In contrast, the original sample consisted of almost exclusively white, highly satisfied married couples from Madison, WI. Within the sample discussed here, we have already observed that lower adolescent neighborhood quality corresponded with increased prefrontal and dACC activation to a social exclusion task ( Gonzalez et al , 2015 ). Others have reported that lower social status is linked to threat-related appraisals of ambiguous social stimuli (e.g.…”
Section: Discussionsupporting
confidence: 52%
“…In young adults, low childhood SES, retrospectively reported, was associated with greater distress and reduced right ventrolateral prefrontal cortex activation in response to social exclusion (Yanagisawa et al 2013). In another study with young adults, low neighborhood quality at age 13 was associated with greater activations in dorsomedial prefrontal cortex, superior frontal gyrus, and dorsal anterior cingulate cortex during social rejection (Gonzalez et al 2014). These increased neural activations among individuals from SED backgrounds suggest a need for greater recruitment of these brain regions in order to regulate emotions during social rejection.…”
Section: Brain: Functionmentioning
confidence: 93%
“…Many studies employed a Cyberball task (Eisenberger, Lieberman, & Williams, 2003;Williams & Jarvis, 2006) to investigate the neural correlates of social inclusion and exclusion in health (Gonzalez, Beckes, Chango, Allen, & Coan, 2014;van der Meulen et al, 2017;Wasylyshyn et al, 2018) and illness (Domsalla et al, 2013;Kumar et al, 2017). In the Cyberball tasks, by observing players tossing a ball to fellow players or with themselves engaged in the game, participants were involved in the dynamics of social interactions.…”
Section: Introductionmentioning
confidence: 99%